Brussels housing atlas of residential building types - Ledent, Gérald; Porotto, Alessandro 1987-; Borret, Kristiaan 1966- (Birkhäuser, 2025)
Modern urban terraced houses or row houses emerged in Europe from the 17th century onwards. Usually two to three storeys high and with a garden at the back, they formed the traditional urban block. In Brussels, this bourgeois form of housing took on a particularly varied and inspiring form - including the well-known Art Nouveau residences - and forms the DNA of the city to this day. This publication analyses 100 selected examples illustrating the emergence of the terraced house and its further development in other forms of housing. The result is a broad panorama and a history of the architecture and development of the city of Brussels with its particularly heterogenous cityscape